A Survey on women's entrepreneurship and innovation (UN New YorkUS, 2014)
Aims to investigate the drivers of entrepreneurship and innovation according to gender in both developed and developing economies; examines impediments to entrepreneurship and innovation and analyse whether these impediments vary by gender and development context; and provides recommendations for policy in the area of women entrepreneurshipm, fostering a greater level of innovation in women-owned enterprises.
Keywords: ENTREPRENEURS